y ′ ′ + 6 y ′ + 9 y = x 2 + x e − 3 x + cos x
Which of the options below is the solution y = y ( x ) of the differential equation above?
A: B: C: D: c 1 e − 3 x + c 2 x e − 3 x + 9 x 2 + 5 0 3 sin x + 2 5 2 cos x c 1 e − 3 x + c 2 x 3 e − 3 x + 9 x 2 − 2 7 4 x + 5 0 3 sin x c 1 e − 3 x + c 2 x e − 3 x + 6 1 x 2 e − 3 x + 9 x 2 − 2 7 4 x + 2 7 2 + 5 0 3 sin x − 2 5 2 cos x c 1 e − 3 x + c 2 x e − 3 x + 6 1 x 3 e − 3 x + 9 x 2 − 2 7 4 x + 2 7 2 + 5 0 3 sin x + 2 5 2 cos x
(This problem is part of the set Extraordinary Differential Equations .)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Integrating factors in linear differential equations
We first solve the corresponding homogeneous equation y ′ ′ + 6 y ′ + 9 y = 0 . Using the roots of the auxiliary equation x 2 + 6 x + 9 = 0 which is − 3 , we get the first component of the homogeneous solution y h , 1 = c 1 e − 3 x . Trying u ( x ) = x as a possible integrating factor gives the second linearly-independent component of the homogeneous solution y h , 2 = c 2 x e − 3 x . Thus, the homogeneous solution is y h = c 1 e − 3 x + c 2 x e − 3 x
For the particular solution we can use the method of undetermined coefficients by trialling y p = k 1 x 2 + k 2 x + k 3 + k 4 x 3 e − 3 x + k 5 sin x + k 6 cos x
Then we get y p ′ ′ + 6 y p ′ + 9 y p = 9 k 1 x 2 + ( 1 2 k 1 + 9 k 2 ) x + ( 2 k 1 + 6 k 2 + 9 k 3 ) + 6 k 4 x e − 3 x + ( 8 k 5 − 6 k 6 ) sin x + ( 6 k 5 + 8 k 6 ) cos x
Comparing this with the RHS of the original ODE gives us the following system of linear equations:
9 k 1 = 1
1 2 k 1 + 9 k 2 = 0
2 k 1 + 6 k 2 + 9 k 3 = 0
6 k 4 = 1
8 k 5 − 6 k 6 = 0
6 k 5 + 8 k 6 = 1
Therefore k 1 = 9 1 , k 2 = − 2 7 4 , k 3 = 2 7 2 , k 4 = 6 1 , k 5 = 5 0 3 , k 6 = 2 5 2 .
(I'll leave it to the reader to determine why k 4 x 3 e − 3 x was used in the the trial solution instead of k 4 x 2 e − 3 x .)